Individually lucky, collectively powerful: a response to friends. Issue 2 (4th May 2021) - Dowding, Keith
ABSTRACT: This paper responds to commentators on the reissue of Keith Dowding, Rational Choice and Political Power . I discuss how powerlessness depends upon collective action problems, the nature of systematic luck, and their interaction with individual responsibility. I defend measurement in conceptual analysis, discuss vagueness and ambiguity and the incoherence of some social concepts. I defend power as a simple notion whose context suggest different extensions. I discuss the conceptual and predictive use of models. I defend 'rationality' as consistency which stands for lawlike regularity. Finally, I discuss the problems raised with my account of persuasion in terms of manipulation.